An Investigation of the Implementation of Peer Feedback Activities in Higher Education - Haryana, Lia; Puspa, Adelia; Saputra, Dwi Bayu (Universitas Cokroaminoto Palopo, 2025)
Peer feedback is frequently studied in English as a second or foreign language (ESL/EFL) writing. Many studies focused on the effect of peer feedback on ESL/EFL students’ writing ability. However, limited studies have examined non-English education students’ perceptions of peer feedback. Therefore, this study aimed to investigate non-English students’ experiences implementing peer feedback activities and their perceptions of peer feedback activity in their writing. This study involved 157 students from 3 different major or study programs of 2 faculties. The participants are students who have just undertaken a general English course. The data were collected through an online questionnaire to examine students’ perceptions of peer feedback activity and semi-structured interviews to draw more pictures of students’ experiences implementing peer feedback activity. The results showed that students had overall high/positive perceptions of peer feedback activity. The majority of the students agree that doing peer feedback is beneficial; has improved their critical thinking; has made them learn a lot from their friends’ mistakes; has facilitated their involvement in social interaction; and has enhanced their awareness of errors in their writing.